2022
DOI: 10.3389/fimmu.2022.868983
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cellular Immunity and Differentially Expressed Immune-Related Genes in Patients With Systemic Sclerosis–Associated Pulmonary Arterial Hypertension

Abstract: Systemic sclerosis (SSc) is the most common connective tissue disease causing pulmonary hypertension (PAH). However, the cause and potential immune molecular events associated with PAH are still unclear. Therefore, it is particularly essential to analyze the changes in SSc-PAH–related immune cells and their immune-related genes. Three microarray datasets (GSE22356, GSE33463, and GSE19617) were obtained by the Gene Expression Omnibus (GEO). Compared with SSc, we found neutrophils have a statistically higher abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…In chronic inflammatory or autoimmune diseases, the high expression of inflammatory cytokines drives neutrophils to form neutrophil extracellular traps (NETs). The number of neutrophils in peripheral blood may reflect the infiltration of neutrophils into tissues ( 64 ). Our results showed that ENST00000313807 and NON-HSAT194388.1 in plasma cirexos were positively correlated with the absolute value and percentage of neutrophils in serum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In chronic inflammatory or autoimmune diseases, the high expression of inflammatory cytokines drives neutrophils to form neutrophil extracellular traps (NETs). The number of neutrophils in peripheral blood may reflect the infiltration of neutrophils into tissues ( 64 ). Our results showed that ENST00000313807 and NON-HSAT194388.1 in plasma cirexos were positively correlated with the absolute value and percentage of neutrophils in serum.…”
Section: Discussionmentioning
confidence: 99%
“…However, hsa-miR-29a-3p in the plasma cirexos was negatively correlated with the percentage of neutrophils in serum. Tu et al ( 64 ) found that the number of neutrophils in peripheral blood of patients with SSc increased significantly. Wareing et al ( 65 ) observed that higher neutrophil counts predicted a worse ILD course and higher long-term mortality in patients with SSc-ILD.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the significant overexpression of RPS27A could enhance the chemoresistance of CML cells to imatinib by trans-activating STAT3 ( Wang et al, 2016 ). However, several studies have identified considerable upregulation of RPS27A expression in the left ventricular myocardium of rats suffering from end-stage PAH (MCT-induced PAH rat model), and abnormal expression of RPS27A has been detected in the peripheral blood of patients with connective tissue disease-associated PAH, and its key regulatory role in the pathogenesis of PAH has been identified ( Hołda et al, 2020 ; Tu et al, 2022 ). Altogether, these findings confirmed that the blood-derived hub transcriptomes are associated with infiltrations of immune cells, hypoxia, and metabolism (glycolysis and fatty acid), which in turn regulates the aberrant vascular remodeling in PAH.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics tools has been widely applied in oncology to identify genetic changes and new potential biomarkers associated with various diseases [14][15][16] . Likewise, researchers have tried to apply bioinformtics analysis in the study of PH to to elucidate the potential functions of circRNAs related to PH, mostly based on databases and animal experiments [17][18][19][20][21][22][23][24][25][26] . However, few studies have utilized clinical samples with definite diagnosis of PH, and researches for PH in COPD are even fewer.…”
Section: W I T H D R a W N S E E M A N U S C R I P T D O I F O R D E ...mentioning
confidence: 99%